2014
DOI: 10.1128/mbio.01464-14
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus gattii in North American Pacific Northwest: Whole-Population Genome Analysis Provides Insights into Species Evolution and Dispersal

Abstract: The emergence of distinct populations of Cryptococcus gattii in the temperate North American Pacific Northwest (PNW) was surprising, as this species was previously thought to be confined to tropical and semitropical regions. Beyond a new habitat niche, the dominant emergent population displayed increased virulence and caused primary pulmonary disease, as opposed to the predominantly neurologic disease seen previously elsewhere. Whole-genome sequencing was performed on 118 C. gattii isolates, including the PNW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
151
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(163 citation statements)
references
References 58 publications
9
151
1
2
Order By: Relevance
“…The WGST data showed clearly that the VGIIc genotype responsible for the most recent infections in the Pacific Northwest is genetically distinct from both VGIIa and VGIIb Vancouver Island outbreak subtypes and suggest that all three subtypes are equally distinct from each other (52). Similar findings based on multilocus sequence typing (MLST) and MLMT analyses, which have been confirmed based on WGST, have been reported recently (53)(54)(55). All studies suggest that the three subtypes have arisen as a result of recombination events that took place prior to their introduction into the Pacific Northwest.…”
Section: Phylogenetic Studies and Molecular Subtypingsupporting
confidence: 73%
See 1 more Smart Citation
“…The WGST data showed clearly that the VGIIc genotype responsible for the most recent infections in the Pacific Northwest is genetically distinct from both VGIIa and VGIIb Vancouver Island outbreak subtypes and suggest that all three subtypes are equally distinct from each other (52). Similar findings based on multilocus sequence typing (MLST) and MLMT analyses, which have been confirmed based on WGST, have been reported recently (53)(54)(55). All studies suggest that the three subtypes have arisen as a result of recombination events that took place prior to their introduction into the Pacific Northwest.…”
Section: Phylogenetic Studies and Molecular Subtypingsupporting
confidence: 73%
“…More recent studies support the proposal that C. gattii molecular type VGII originated in South America (46,72) and that Australia and Thailand are possible "stepping stones" in the global spread of VGIIb from South to North America (88,89). The introduction of VGIIb from its ancestral origin in South America, via different parts of the world, has recently been confirmed by using WGST (54). These findings agree with a recent comprehensive, global study of VGII strains, which traced the origin of both outbreak subgenotypes VGIIa and VGIIb back to an ancestral C. gattii strain, LMM645, from the Amazon rainforest.…”
Section: Global Distribution and Movement Of C Gattii Genotypesmentioning
confidence: 50%
“…Although the VGII subtypes were found to be completely clonal, the overall VGII population showed a high genetic diversity. In addition, several mutations, deletions, transpositions and recombination events have been identified within VGII strains, and this pointed to a South American origin 30 . Using WGS to compare subtypes, various genetic differences have been recognised, which are potentially related to habitat adaptation, virulence, and pathology 30 .…”
Section: Molecular Type and Species Identificationmentioning
confidence: 98%
“…In addition, several mutations, deletions, transpositions and recombination events have been identified within VGII strains, and this pointed to a South American origin 30 . Using WGS to compare subtypes, various genetic differences have been recognised, which are potentially related to habitat adaptation, virulence, and pathology 30 . For example, a set of~50 genes has been identified being either present or absent in lung or brain infecting strains …”
Section: Molecular Type and Species Identificationmentioning
confidence: 98%
“…Comparative genomic studies have identified genes that are particular to the high virulence strains but their role in virulence is yet to be verified 11,12 . As secreted biomolecules are mediators of contact between the host and the pathogen, differences in these are likely to influence whether a pathogen will be rapidly recognized and eliminated, or will be able to bypass the host response and use host resources to establish an active infection.…”
mentioning
confidence: 99%